«Քաղաքական գիտակցություն» եզրույթը և զինծառայողների քաղաքական գիտակցությունը - Թորոսյան, Դավիթ (ԱԵԳՄՄ հրատ.)
The purpose of the article is to present the concept of "political consciousness", its formation, development and establishment as a subjective aspect of politics. The article poses as a key issue the study of existing views on the political consciousness of military personnel, the refutation of common false approaches, and the promotion of new approaches to the political consciousness of military personnel. To realize the set goal and solve problems, dialectics (involving the observation of phenomena in the course of movement, development and change), as well as revealingdescriptive and other methods were used. The work was written using a joint examination of facts, historical, historical-comparative, nomothetic, ideographic and a number of other methods. The conclusions that were drawn from the analysis were remarkable, especially against the background of the new interpretation of the term “political consciousness” and taking into account the political consciousness of military personnel, free from political chaos. As a result of a professional interpretation of the concept of political consciousness, we came to the conclusion that political consciousness represents a socio-political context and is aimed mainly at the formation of stable social and political values, ideas, approaches and beliefs among the masses, groups and individuals. Accordingly, prohibitions on the direct participation of military personnel in the political life of society do not at all mean that they should not have political consciousness, because the term “political consciousness” is associated not only with joining parties and participating in “political chaos”. Цель статьи – представить понятие «политическое сознание», его становление, развитие и становление как субъективный аспект политики. В статье в качестве ключевого вопроса рассматривается изучение существующих взглядов на политическое сознание военнослужащих, опровержение распространенных ложных подходов, продвижение новых подходов к политическому сознанию военнослужащих. Для реализации поставленной цели и решения задач мы использовали диалектический (предполагающую наблюдение явлений в ходе движения, развития и изменения), а также описательный метод, а также методы, нацеленные на выявления новых фактов. Работа написана с использованием синтетического изучения фактов, исторического, историко-сравнительного, номотетического, идеографического и ряда других методов. Выводы, ставшие результатом проведенного анализа, оказались примечательны, особенно в контексте новой трактовки термина «политическое сознание» и с учетом политического сознания военнослужащих, свободного от «политического хаоса». В результате профессиональной интерпретации понятия политического сознания мы пришли к выводу о том, что политическое сознание представляет собой социально-политический контекст и направлено главным образом на формирование устойчивых социальных и политических ценностей, идей, подходов и убеждений среди масс, отдельных групп и личностей. Соответственно, запреты на прямое участие военнослужащих в политической жизни общества вовсе не означают, что они не должны обладать политическим сознанием, поскольку термин «политическое сознание» связан не только с вступлением в различные партии и участием в политическом хаосе.
Keywords: Քաղաքագիտություն; Զինվորական ծառայություն